PENGUKURAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL & FRAKSI ETIL ASETAT DAUN JERUK PURUT (Citrus hystrix DC) DENGAN METODE SPEKTROFOTOMETRI UV-VIS - Rizky Saputra, Dewa; Melati, Rika; Karimah, Umul (Universitas Nahdlatul Ulama Kalimantan Timur, 2023)
This study measured the total flavonoid content of 70% ethanol extract and the ethyl acetate fraction of kaffir lime leaves (Citrus hystrix DC). The purpose of this study was to measure the total flavonoid content of the 70% ethanol extract and the ethyl acetate fraction of kaffir lime leaves (Citrus hystrix DC). Extraction of the chemical content of kaffir lime leaves (Citrus hystrix DC) was carried out by maceration and remaceration extraction processes using ethanol and to measure the metabolite compounds. flavonoids in total and separate other metabolites by a fractionation process,). Measurement of total flavonoid content of ethanol extract and ethyl acetate fraction by UV-Vis spectrophotometry. The results showed that the total flavonoid content of kaffir lime leaves (Citrus DChystrix DC) from the ethanol extract contained a total flavonoid content of 14,380 mgQE/g and the ethyl acetate fraction contained a total flavonoid content of 44,287 mgQE/g.